After Act 10: a Wisconsin district administrator's account of teacher compensation - Larson, Margaret Francis Collins (My University, 2018)
The passage of Wisconsin Act 10 in 2011 ended an era. In 1959, the State of Wisconsin was the first to allow local government workers the ability to organize, which allowed employees to negotiate with employers for wages, hours, and conditions. In 1972, the Wisconsin Education Association Council formed. The group became a powerful and influential organization. As power grew, so did teacher salaries and benefits. Politicians became increasingly concerned with the tax impact these benefits caused (Umhoefer, 2016). Several governors took office and attempted to limit collective bargaining, but not until Governor Scott Walker did it go so far as to eliminate collective bargaining. In 2011, Governor Scott Walker passed the Wisconsin Act 10. This law, recognized as the Budget Repair Bill, was an effort to improve the state’s fiscal problems. However, a portion of these efforts entailed limiting state aid to local governments, which resulted in a $792 billion tax cut to state school districts (Szafir, Flanders, & Hudson, 2016). To compensate for the difference, Governor Walker provided school districts with an alternative means, or tools as he described them, of controlling costs. These alternative means allowed district administrators to change existing policies surrounding teacher compensation, hiring, firing, and best practices without the approval of the teachers’ unions. The purpose of this study was to examine how one district administrator managed teacher compensation since the implementation of the Wisconsin Act 10 in 2011. This study focused on the self-reflection and personal analysis of the author, the district administrator of a school district in Wisconsin, and her personal experiences surrounding policy changes to teacher compensation following the passing of Wisconsin Act 10. Few studies have considered how teacher compensation entails involvement of the district administrators, the associated challenges these professionals must face, and how such challenges are resolved.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Education - Educational Leadership and Policy Superintendent Licensure
Keywords: Teachers--Salaries, etc.--United States